Victims Of Dating Violence Are Reviewed From Peer Group Emotional Support - Ina Sarah Sarlita Moy (Universitas Katolik Soegijapranata, 2019)
The purpose of this study focuses on handling victims of courtship violence (KDP) through peer group emotional support. The characteristics of the peer group lead to emotional attachments such as a sense of belonging, love, closeness, trust, and acceptance by the group, which is not obtained from parents. Through peer groups, subjects are more free to tell stories, feel comfortable, safe, get solutions, attention and affection, even though conflicts sometimes occur. This study used the Participatory Action Research (PAR) method with a qualitative approach, namely through interview techniques, FGDs, evaluation, sharing and verbal and non-verbal motivation and recreation. Participants are domiciled in the city of Salatiga consisting of four people, one subject and three peer group members, with the same characteristics of age and sex, having friends for 2 years, having experienced KDP, and knowing the violence experienced by the subject. The results showed that although some social media through WhatsApp group (sharing quotes motivation) each other and members of the peer group experienced KDP, the subjects felt that there was emotional support finding identity, feeling confident, feeling valuable and being accepted. The next recommendation that can be given to the subject therapy for self-recovery or reconciliation with him and his ex-girlfriends such as Cognitive Behavior Therapy (CBT) and relationship restoration.